Reasons for wage rigidity in Germany - Wolfgang Franz; Friedhelm Pfeiffer (Institute for the Study of Labor (IZA), 2006)
This study investigates institutional and economic reasons for downward wage rigidity regarding three occupational skill groups. Based on a survey of 801 firms in Germany and an econometric analysis, we find strong support for explanations based on the effects of labour union contracts and efficiency wages that differ between skill groups. Survey respondents indicate that labour union contracts and implicit contracts are important reasons for wage rigidity for the (less) skilled. Specific human capital and negative signals for new hires are causes of the stickiness of wages for the highly skilled. Compared with US evidence, German firms seem to attach more importance to labour union contracts and specific human capital.
Keywords: J41; J51; K31; 330; wage rigidity; labour union contracts; efficiency wage theory; implicit contract theory; regulation of labour; Lohnrigidität; Institutionalismus; Beruf; Effizienzlohn; Tarifvertrag; Deutschland